Ingresos Y Gastos De “Comercial Sandy” - Freire Litardo, Sandy Lisbeth (2017)
The present case study is oriented to know about the income and expenses of commercial Sandy, taking into account that accounting records for decision making are indispensable and important, this importance is recognized and accepted by the owner considering the benefits in productivity and economy, in addition to generating the necessary information to cancel taxes to the State. It should be noted that the entity has the purpose of ensuring that its economic activities are effective and generate income through the application of techniques and methods to record all operations that are performed, which requires accounting systems that include the instructions and capitals used by the entity, for a control of the financial activities in a useful way on the dispositions of the entity. It was prepared and used sources of information necessary for the research work to be fruitful and thus meet the objective of the study. The objective of the case study is to determine how Sandy's revenues and expenses are recorded, as well as generate knowledge about the administration, where they obtain the main revenues, verify if the accounting information is generated and presented in a timely manner, collect all necessary information on the entity and the result of its operational activities.